2016
DOI: 10.1007/s00784-016-1839-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of inter-appointment endodontic flare-ups and host-related factors

Abstract: This article provides evidence that patients suffering from inflamed pulp will not develop flare-up if adequate cleaning and shaping of the root canal space was performed. It also shows that patients above the age of 50 are a high-risk group that is prone to flare-up development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 29 publications
7
46
0
6
Order By: Relevance
“…An important clinical situation resulting from apically extruded debris during endodontic therapy has to do with flare-up, which consists of acute exacerbations of an asymptomatic pulpal and/or periradicular pathologic condition. This condition is not desirable for patients and clinicians, and may happen from 2 -3.2% of the cases (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…An important clinical situation resulting from apically extruded debris during endodontic therapy has to do with flare-up, which consists of acute exacerbations of an asymptomatic pulpal and/or periradicular pathologic condition. This condition is not desirable for patients and clinicians, and may happen from 2 -3.2% of the cases (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The flare-up rate varies widely in the literature due to differences in the variables studied, and the methods used to characterize flare-up [3,4,6,37]. In the present study, a definition proposed by Ehrmann et al was used to identify flare-up because of its well-defined criteria.…”
Section: Discussionmentioning
confidence: 89%
“…In the literature, such acute exacerbation of pain is coined a "flare-up" [2]. The rate of flare-up varies from 1.5% to 12.3% [3][4][5][6]. The etiology of postoperative pain is multifactorial and complex.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, no difference was found in terms of age between groups similar to previous studies. 23,24 However, Azim et al 25 reported higher risk for the patients >50 years in developing flare-ups.…”
Section: Discussionmentioning
confidence: 99%